How do EU norms diffuse? Rule of law promotion in EU-China cooperation on environmental governance. Issue 1 (2nd January 2017) - Yang, Yifan
Abstract: The rule of law (RoL), as a highly valued international principle and one of the founding principles of the European Union (EU), plays a significant role in its environmental governance. Overlapping interests between China's search for effective solutions to environmental problems and the EU's environmental governance experience provide a solid ground for bilateral cooperation in environmental area, and the RoL which is embodied in these bilateral programmes has also been diffused to China. Through looking at the top-down approach of capacity building in law enforcement and the bottom-up approach of the raising of public awareness of environmental rights and public participation promotion, China's lesson-drawing and the EU's RoL promotion in EU-China Environmental Governance Programme can be understood. Moreover, although studying the long-term effect of RoL promotion requires more empirical data, this paper does explain how EU norms diffuse in practice.